STRATEGY RAISING ZAKAT, INFAQ, AND SHADAQAH FUNDS AT THE NATIONAL AMIL ZAKAT AGENCY WEST KALIMANTAN PROVINCE IN THE PERSPECTIVE OF DA'WAH MANAGEMENT - Fatmawati, Rohima (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2024)
The background of this research is the researcher's interest in describing fundraising strategies in collecting zakat, infaq and shadaqah funds in 2018. The aim of this research is to find out, 1) The method used by the West Kalimantan Province National Amil Zakat Agency (BAZNAS) in carrying out fund collection zakat, infaq and sadaqah. 2) Obstacles faced by the National Zakat Amil Agency (BAZNAS) of West Kalimantan Province in collecting zakat, infaq and shadaqah funds. 3) Solutions implemented by the National Zakat Amil Agency (BAZNAS) of West Kalimantan Province to overcome the problem of collecting zakat, infaq and shadaqah funds.This research uses descriptive research methods with a qualitative approach. Data sources are divided into two, namely primary data and secondary data. The data collection techniques that researchers used were observation and in-depth interviews as well as documentation. The data collection tools used in this research are observation guidelines, interview guidelines, and documents. Meanwhile, the analysis techniques in this research are data reduction, data display and conclusion drawing.Based on the research that has been carried out, it can be concluded that: 1) the methods used by BAZNAS in collecting funds using the direct method are socialization, cash deposits and pick-up services. Meanwhile, indirect methods are print and electronic media, online media, and transfers. 2) The obstacles experienced by BAZNAS West Kalimantan Province are the lack of public awareness of the importance of zakat, inappropriate timing of activities, and several agencies that directly pay zakat to the central BAZNAS in Jakarta. 3) the solution taken by BAZNAS to solve the problem that occurred was to form da'i-da'i in every province in West Kalimantan and continue to carry out outreach and understanding to agencies that have not paid their zakat in BAZNAS West Kalimantan Province, as well as providing understanding in accordance with Al-Qur'an and Hadith as well as Law No. 23 of 2011. In determining the time of activities, confirm and coordinate first with the relevant agencies so that there are no clashes with activity times.Keywords: Strategy, collection, method, zakat